2011
DOI: 10.3109/13697137.2010.520099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and metabolic effects of drospirenone–estradiol in menopausal women: a prospective study

Abstract: In postmenopausal women, E2+DRSP administration improves vasomotor symptoms and general aspects of quality of life and may positively influence cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
(36 reference statements)
0
27
0
4
Order By: Relevance
“…One meta-analysis of 21 studies, states that the HT is highly effective in alleviating hot flushes and night sweats; however, in women who were randomized to placebo, a 50.8% reduction in hot flushes was observed between baseline and the end of the study [47]. In a RCT, Gambacciani showed that HT improves significantly life quality and has a positive influence on cardiovascular risk factors [48]. Another meta-analysis states that HT reduces abdominal obesity, insulin resistance, new-onset diabetes, lipids, blood pressure, adhesion molecules and procoagulant factors in women without diabetes and reduced insulin resistance and fasting glucose in women with diabetes [49].…”
Section: Climacteric Syndromementioning
confidence: 92%
“…One meta-analysis of 21 studies, states that the HT is highly effective in alleviating hot flushes and night sweats; however, in women who were randomized to placebo, a 50.8% reduction in hot flushes was observed between baseline and the end of the study [47]. In a RCT, Gambacciani showed that HT improves significantly life quality and has a positive influence on cardiovascular risk factors [48]. Another meta-analysis states that HT reduces abdominal obesity, insulin resistance, new-onset diabetes, lipids, blood pressure, adhesion molecules and procoagulant factors in women without diabetes and reduced insulin resistance and fasting glucose in women with diabetes [49].…”
Section: Climacteric Syndromementioning
confidence: 92%
“…On the other hand, clinical studies performed in normotensive women did not report any effect of DRSP on BP. In a group of 30 women randomly treated with either DRSP 2 mg/E2 1 mg or with NETA 0.5 mg/E2 1 mg, no significant difference was observed in 24-hour, daytime, and nighttime BP values 98. In another Italian study, postmenopausal women were treated with E2 (1 mg/day) plus DRSP (2 mg/day).…”
Section: Ht In Normotensive Womenmentioning
confidence: 94%
“…Отличительной особенностью проведенного нами исследования является длительность использования МГТ фиксированной комбинацией Е2 1 мг/ДРСП 2 мг -5,2 [12,13]. ДРСП является прогестагеном со свойствами анта-гониста рецепторов к альдостерону, т.е.…”
Section: Endothelial Dysfunction In Early Postmenopausal Women эндотеunclassified
“…обладает уни-кальными свойствами, не характерными для других синтетических прогестагенов. ДРСП способствует сни-жению АД, стимулирует выработку NO путем связы-вания с прогестероновыми и минералокортикоидны-ми рецепторами, расположенными на эндотелиоци-тах, запускает негеномный и геномный пути синтеза NO, не препятствуя синтезу NO, индуцированному эстро-генами [12,13]. Способность ДРСП снижать АД, пре-пятствовать увеличению объема висцерального жира, благоприятно влиять на липидные изменения крови и выраженность проявлений метаболического синдро-ма может быть еще одним механизмом благоприятного влияния на структурно-функциональное состояние сосудов [5].…”
Section: Endothelial Dysfunction In Early Postmenopausal Women эндотеunclassified